1998
DOI: 10.1530/eje.0.1390454
|View full text |Cite
|
Sign up to set email alerts
|

Local action of exogenous growth hormone and insulin-like growth factor-I on dihydroxyvitamin D production in LLC-PK1 cells

Abstract: Previous in vivo studies have shown that growth hormone (GH) affects vitamin D and mineral metabolism. Insulin-like growth factor-I (IGF-I) was recently reported to be a regulator of renal 1,25-dihydroxyvitamin D 3 (1,25-(OH) 2 D 3 ) production, suggesting that it mediates the effects of GH on vitamin D metabolism. However, there is no direct evidence to support this. The present study was designed to investigate the in vitro effects of GH and IGF-I on the renal production of 1,25- (OH) produced were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 33 publications
1
28
0
1
Order By: Relevance
“…kidney cells in vitro (51). Our findings indicate that the well-documented in vitro stimulation of vitamin D metabolism by IGF-I (52, 53) could be relevant in vivo.…”
Section: Discussionsupporting
confidence: 55%
“…kidney cells in vitro (51). Our findings indicate that the well-documented in vitro stimulation of vitamin D metabolism by IGF-I (52, 53) could be relevant in vivo.…”
Section: Discussionsupporting
confidence: 55%
“…Several studies have demostrated that IGF-I is a stimulatory factor of renal and placental 1,25-(OH) 2 D synthesis [1][2][3][4][5][6][7][8][9][10][11][12]. These observations prompted us to study longitudinal changes of 1,25-(OH) 2 D and IGF-I serum levels in pregnant women who remained normotensive and to determine whether alterations in circulating levels of these two hormones could be observed in women before they developed PE.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that insulin-like growth factor I (IGF-I) stimulates renal 1,25-dihydroxyvitamin D (1,25-(OH) 2 D) production in nonpregnant human and rodents [1][2][3][4][5][6][7][8][9][10]. In addition, previous results from this laboratory showed a stimulatory effect of IGF-I on placental 1,25-(OH) 2 D synthesis [11,12], indicating that this growth factor could be a physiological regulator of Vitamin D metabolism during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…It has long been known that insulin-like growth factor 1 (IGF1) causes an increase in the circulating levels of 1,25-dihydroxyvitamin D (1,25(OH) 2 D), the hormonally active vitamin D metabolite, by stimulating the expression and activity of the 1a-hydoxylase that produces 1,25(OH) 2 D in the kidney (1,2). Indeed, plasma 1,25(OH) 2 D is significantly higher in active than controlled acromegaly, with a tendency to hypercalcemia, hyperphosphatemia, and hypercalciuria (3).…”
Section: Introductionmentioning
confidence: 99%